The Influence of Single Parenting on Children's Character Development in Tembelok Neighborhood, Sandubaya District, Mataram City - Syahida, Alfia; Ningsih, Dewi Puspita; Apriawan, Andika; Mulyan, Andi (Primary Journal of Multidisciplinary Research, 2025)
This study examines the influence of single parenting on children's character development in the Tembelok neighborhood, Sandubaya District, Mataram City. Using a descriptive qualitative approach, data were collected through observation, structured interviews, and documentation with single parents, children, and community leaders. The findings reveal that despite economic constraints and the dual roles faced by single parents, the dominant parenting style applied is authoritative, characterized by warmth, consistency, and clear but flexible rules. Daily practices such as greetings, respect for elders, discipline in worship, and participation in communal activities (e.g., religious events, mutual cooperation, and traditional ceremonies) foster positive character traits including honesty, discipline, responsibility, empathy, and religiosity. The study also identifies three key factors influencing parenting outcomes: limited economic resources, educational background of parents, and the role of social support from extended family and community networks. These results highlight the importance of authoritative parenting combined with communal and cultural values in shaping children’s moral and social development. Practically, the study suggests that community-based programs and social protection policies are needed to strengthen the capacity of single parents in raising resilient and well-rounded children.